Implanted Neuroprosthesis for Assisting Arm and Hand Function after Stroke: A Case Study - Knutson, Jayme S. (2012)
Loss of arm and hand function is common after stroke. An implantable 12-channel electromyogram (EMG)-controlled functional electrical stimulation neuroprosthesis (NP) may be a viable assistive device for upper limb hemiplegia. In this study, a research participant 4.8 yrs post-stroke underwent pre-surgical screening, surgical installation of the NP, training, and assessments of upper limb impairment, activity limitation, and satisfaction over a 2.3-yr period. The NP increased active range of finger extension from 3 to 96 degrees, increased lateral pinch force from 16 to 29 N, increased the number of objects from 1 to 4 out of 6 that the participant could grasp and place in a Grasp-Release Test, and increased the Arm Motor Abilities Test score by 0.3 points. The upper limb Fugl-Meyer score increased from 27 at baseline to 36 by end-of-study. The participant reported using the NP at home 3–4 days/wk, up to 3 hrs/day for exercise and household tasks. The effectiveness of the NP to assist with ADL was dependent on the degree of flexor tone, which varied with task and level of fatigue. The EMG-based control strategy was not successfully implemented; button presses were used instead. Further advancements in technology may improve ease of use and address limitations caused by muscle spasticity.